THE EFFECTIVENESS OF USING THE POGO ANAGRAM GAME TO INCREASE VOCABULARY MASTERY OF TENTH GRADE STUDENTS AT SMK NU PACE - Peni Pajar Riana Pajar Riana; Henny Roeswllaningtyas (Journal of English Language Education, 2025)
This study aims to analyze the effectiveness of using Pogo Anagram Game in improving vocabulary mastery of grade X students at SMK NU Pace in the 2023/2024 academic year. The method used in this study was an experiment with a pre-test and post-test design, involving 29 students from the X TKJ-2 class. Data was collected through pre-test and post-test to measure students' vocabulary mastery before and after the application. The results showed that the average score of students' pre-test was 60, which indicated unsatisfactory vocabulary mastery. After the implementation of the Pogo Anagram Game, the average post-test score increased to 80, indicating a significant improvement in students' vocabulary acquisition. Statistical analysis using t-test resulted in a t-count value >= 1.699 (at 5% significance level and degree of freedom = 28), which confirms that there is a significant difference between pre- and post-learning vocabulary acquisition. The conclusion of this study is that Pogo Anagram Game is effective in improving students' vocabulary acquisition. The findings make an important contribution to the development of innovative and engaging learning methods, and demonstrate the potential of using educational games in the context of English language learning. This research is expected to be a reference for educators in implementing more interactive and fun learning methods to improve students' learning outcomes.